VAKSINASI RABIES PADA ANJING OLEH PEMILIK DAN FAKTOR YANG BERHUBUNGAN SELAMA PANDEMI COVID-19 DI WILAYAH SANUR, DENPASAR - Wauran, Mary Amalia; Subrata, I Made (ARCHIVE OF COMMUNITY HEALTH; Vol 9 No 1 (2022): April 2022DO - 10.24843/ACH.2022.v09.i01.p06, 2022)
Rabies can be prevented and managed effectively through routine rabies vaccinations for dogs, with vaccination coverage reaching 70% to form herd immunity. The emergence of the Covid-19 pandemic caused the implementation of rabies vaccination for dogs in The Sanur Region to experience limitations, resulting in a decrease in rabies vaccination coverage. The purpose of this study was to determine rabies vaccination in dogs by owners and related factors during the Covid-19 pandemic in the Sanur area, based on the Precede-Proceed Model theory by Lawrence Green. This study uses a quantitative analytical observational method with cross-sectional design. The study was conducted from March to May 2021, using primary data from 155 dog owners who live in The Sanur Region of Denpasar, and were selected based on proportional random sampling. Primary data collected from online questionnaires were analyzed in three stages, descriptive analysis, different proportion test (chi square), and logistic regression test. The results of the analysis using the chi square test and logistic regression showed that only three variables had a significant influence on the behavior of dog owners in giving rabies vaccinations for their dogs during the Covid-19 pandemic, namely education (OR=140.68;95%CI:10, 77-1837.64), income (OR=13.04;95%CI:2.98-57.06), and knowledge (OR=32.36;95%CI:9.43-111.08). Keywords: Rabies Vaccination, Dog Owner Behavior